2011
DOI: 10.1371/journal.pone.0018529
|View full text |Cite
|
Sign up to set email alerts
|

Gill Damage to Atlantic Salmon (Salmo salar) Caused by the Common Jellyfish (Aurelia aurita) under Experimental Challenge

Abstract: BackgroundOver recent decades jellyfish have caused fish kill events and recurrent gill problems in marine-farmed salmonids. Common jellyfish (Aurelia spp.) are among the most cosmopolitan jellyfish species in the oceans, with populations increasing in many coastal areas. The negative interaction between jellyfish and fish in aquaculture remains a poorly studied area of science. Thus, a recent fish mortality event in Ireland, involving Aurelia aurita, spurred an investigation into the effects of this jellyfish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 20 publications
10
60
0
Order By: Relevance
“…For example, in April 2014 in AlmerĂ­a and May 2014 in the MĂĄlaga fish farm, gill scores were 6 ± 1.10 and 9.20 ± 0.60, respectively, and jellyfish occurred in medium-high densities (19.71 ± 3.07 ind m −3 in the AlmerĂ­a pen and 48.80 ± 10.79 ind m −3 in the MĂĄlaga facility) but no fish mortalities were reported in these periods. Experimental studies with the scyphozoan A. aurita showed gill epithelium recovery required 2 weeks after even brief (10 h) contact between jellyfish and salmonids (Baxter et al, 2011b). Equally, laboratory experiments carried out by Bosch-Belmar et al (2016b), demonstrated partial recovery of sea bream gill tissue after 3 weeks from fish exposure to medium densities of P. noctiluca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in April 2014 in AlmerĂ­a and May 2014 in the MĂĄlaga fish farm, gill scores were 6 ± 1.10 and 9.20 ± 0.60, respectively, and jellyfish occurred in medium-high densities (19.71 ± 3.07 ind m −3 in the AlmerĂ­a pen and 48.80 ± 10.79 ind m −3 in the MĂĄlaga facility) but no fish mortalities were reported in these periods. Experimental studies with the scyphozoan A. aurita showed gill epithelium recovery required 2 weeks after even brief (10 h) contact between jellyfish and salmonids (Baxter et al, 2011b). Equally, laboratory experiments carried out by Bosch-Belmar et al (2016b), demonstrated partial recovery of sea bream gill tissue after 3 weeks from fish exposure to medium densities of P. noctiluca.…”
Section: Discussionmentioning
confidence: 99%
“…Tiny and almost transparent medusae, siphonophores, and hydrozoan larvae may easily remain unnoticed to aquaculture operators, but they can develop high density blooms, be inhaled by fish, and inflict severe damage due to nematocyst discharge and consequent tissues envenomation (FossĂ„ et al, 2003). A range of morphological injuries caused by contacts with cnidarian stinging cells have been described on several cultured fish species (Baxter et al, 2011b;Bosch-Belmar et al, 2016b;Marcos-LĂłpez et al, 2016). Available evidence shows that a few hours of exposure to stinging cells may lead to severe damage at cellular, tissue and systemic levels, including changes in fish metabolic performances (BoschBelmar et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of man-made barriers is less well documented (Purcell et al, 2007;Doyle et al, 2008;Baxter et al, 2011;Mianzan et al, 2014). The ISCh possess the majority of the country's salmon farms with over 500 fish farms along the ISCh coast (excluding fjords) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Jellyfish blooms have been shown to impact marine food webs (Malej et al, 2007) including the microbial loop (Tinta et al, 2012), limiting food for fish through competition (Pucell & Arai, 2001), harming farmed fish (Baxter et al, 2011), and exacerbating eutrophication phenomena (West et al, 2009). Although jellyfish abundance typically exhibits large inter-annual and decadal fluctuations (Condon et al, 2013), some recent studies have convincingly shown that several anthropogenically mediated factors stimulate the proliferation of jellyfish (Richardson et al, 2009;Purcell, 2012).…”
Section: Discussionmentioning
confidence: 99%